The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1017/s2045796021000196
|View full text |Cite
|
Sign up to set email alerts
|

The treatment gap for mental disorders in adults enrolled in HIV treatment programmes in South Africa: a cohort study using linked electronic health records

Abstract: Aims Mental disorders are common in people living with HIV (PLWH) but often remain untreated. This study aimed to explore the treatment gap for mental disorders in adults followed-up in antiretroviral therapy (ART) programmes in South Africa and disparities between ART programmes regarding the provision of mental health services. Methods We conducted a cohort study using ART programme data and linked pharmacy and hospitalisation data to examine the 12-month prevalence of treatment for me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…The South African estimate is taken from household survey data and programmatic opioid treatment centre data. Our study estimate of 0.1% likely underestimates the true prevalence in this cohort because substance use and mental health disorders often remain undiagnosed and untreated (Demyttenaere et al, 2004;Ruffieux et al, 2021;Seedat et al, 2008). To understand the full extent of the opioid epidemic in South Africa, accurate data from all healthcare sectors are needed.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The South African estimate is taken from household survey data and programmatic opioid treatment centre data. Our study estimate of 0.1% likely underestimates the true prevalence in this cohort because substance use and mental health disorders often remain undiagnosed and untreated (Demyttenaere et al, 2004;Ruffieux et al, 2021;Seedat et al, 2008). To understand the full extent of the opioid epidemic in South Africa, accurate data from all healthcare sectors are needed.…”
Section: Discussionmentioning
confidence: 89%
“…First, our study likely underestimates the incidence of opioid-related disorders because our case definition relied on diagnoses and treatment as proxies for opioid-related disorders. In South Africa, mental health and substance use disorders often remain undiagnosed and untreated (Ruffieux et al, 2021), and our definition of opioid-related disorders would miss individuals with undiagnosed and untreated opioid-related disorders. The stigma attached to substance use disorders (P.W.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, conclusions regarding access to mental health care cannot be generalised to patients accessing public sector HIV care programs. In a previous study, we showed that, in South Africa’s public sector, rates of ascertainment and treatment of mental disorders are much lower than in the private sector [35]. Interventions aimed at addressing the high burden of mental illness amongst people living with HIV are needed in both the public and private sectors in South Africa.…”
Section: Discussionmentioning
confidence: 99%
“…Early detection and effective management of mental disorders among people living with HIV may improve the quality of life of affected individuals, ART adherence and viral load suppression [17,18], thus reducing the incidence of HIV-associated complications, preventing drug resistance and HIV transmission. Despite these benefits, there is a large ‘treatment gap’ in mental health care among people living with HIV in low- and middle-income countries: most people affected by mental illness do not receive appropriate treatment [19,20].…”
Section: Introductionmentioning
confidence: 99%